Official Recognized Boundary of Southeast Alaska Fish Habitat Partnership, 2014 - National Fish Habitat Partnership; Southeast Alaska Fish Habitat Partnership; United States Geological Survey (USGS Science Data Catalog, 2014)
This shapefile is the official boundary of the Southeast Alaska Fish Habitat Partnership. The shapefile was developed in 2014 to reflect the boundary as defined by the Southeast Alaska Fish Habitat Partnership, a recognized Fish Habitat Partnership (FHP) of the National Fish Habitat Partnership.